O064 A Portable Ocular Assessment for Predicting Fitness to Drive under Extended-Wakefulness Conditions – Preliminary Analysis. (9th November 2022) - Bickley, K; Adams, R; Anderson, C; Cori, J; Howard, M; Lack, L; Lovato, N; Stevens, D; Vakulin, A
Abstract: Introduction: In response to the high incidence of fatigue-based vehicle accidents, roadside assessments of sleepiness are in significant demand. For this purpose, we've piloted the existing NeuroFlex® Platform, which takes ocular performance measurements of both prosaccade and antisaccade eye-movements using a portable Virtual Reality (VR) headset. We've conducted preliminary comparisons between these measures and simulated driving performance. Methods: Sixteen young-adults (females= 8; age M= 25.13, SD= 4.30) completed five test batteries starting 1-hour post-wake where repeated testing encapsuled more than 24-hours of extended wakefulness. Each battery consisted of one 60-minute drive on the AusEd driving simulator, in addition to three administrations of 60-second prosaccade and antisaccade assessments using the NeuroFlex® VR platform. Results: Steering deviations from the median lane position showed a time main effect, F(4, 24.49) = 13.38, p <.001, with the most diminished performance occurring at 19 (M=59.50cm, SD=26.61cm) and 25-hours post-wake (M=72.88cm, SD= 40.09cm) (vs. peak performance @13-hours post-wake M=35.09, SD=12.81; M diff.= 24.41 and 37.79 respectively, p <.001). One moderate association between prosaccade latency and steering deviation was found in the final battery following 25-hours of wakefulness (r=.51, p= 0.04). No significant associations were found for antisaccade latency. Discussion: Despite the lack of significant associations with steering deviations, eye-movement latency did demonstrate durational increases over extended wakefulness. In this preliminary investigation we were limited to the existing output generation of the NeuroFlex® platform. Therefore, with refined data analyses of ocular control, we see promise in the NeuroFlex® platforms capability of detecting road users' fitness to drive.